2021
DOI: 10.1002/acr.24184
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Inhibitor Dose Reduction for Axial Spondyloarthritis: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Objective The present study was undertaken to investigate the effectiveness and safety of dose reduction of tumor necrosis factor inhibitor (TNFi) therapy in the treatment of axial spondyloarthritis (SpA) compared to usual care. Methods We searched the Cochrane Central Register of Controlled Trials, Embase, Medline, and trial registries. We screened, extracted data, and assessed risk of bias in duplicate. Data were pooled using random‐effects models; subgroup analyses were performed for type of TNFi, prior TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For TNF inhibitors, an open, non-randomized study showed that, in a population of patients with low disease activity, the outcome was the same over 1 year between continuing with the same regimen and increasing the dosing interval [123]. In the C-Optimise followup study of patients in remission, their condition was stable for 1 year when the certolizumab dose was reduced by 50% However, the experts remind us that a higher risk of disease flares/relapses has been observed when the dose of TNF inhibitors is reduced [125]. The SPACING study is a randomized prospective trial evaluating, in patients who have low disease activity for at least 6 months, standard dosing or increased dosing intervals for TNF inhibitors, with follow-up every 3 months and adjustment of the interval (longer or shorter) based on the disease activity, over 12 months [126].…”
Section: In Patients With Enthesitis Definitely Attributed To Spa or Dactylitis That Does Not Respond To Symptomatic Treatment A Targetedmentioning
confidence: 99%
“…For TNF inhibitors, an open, non-randomized study showed that, in a population of patients with low disease activity, the outcome was the same over 1 year between continuing with the same regimen and increasing the dosing interval [123]. In the C-Optimise followup study of patients in remission, their condition was stable for 1 year when the certolizumab dose was reduced by 50% However, the experts remind us that a higher risk of disease flares/relapses has been observed when the dose of TNF inhibitors is reduced [125]. The SPACING study is a randomized prospective trial evaluating, in patients who have low disease activity for at least 6 months, standard dosing or increased dosing intervals for TNF inhibitors, with follow-up every 3 months and adjustment of the interval (longer or shorter) based on the disease activity, over 12 months [126].…”
Section: In Patients With Enthesitis Definitely Attributed To Spa or Dactylitis That Does Not Respond To Symptomatic Treatment A Targetedmentioning
confidence: 99%
“…As the OL extension portion of this study also showed that improvements in disease activity were maintained in participants who continued GLM for up to 52 weeks, as well as in participants who switched from PBO to GLM, it was reasonable to consider withdrawal treatment paradigms. A recent meta-analysis of randomized controlled trials evaluating lower doses or extended dosing intervals of TNFi (including GLM) used in the treatment of axSpA concluded that maintaining the standard dosing regimen probably improves the sustained effect on disease activity and helps to prevent disease flare [ 13 ]. The present GO-BACK study, which was designed to evaluate both the effect of GLM withdrawal on disease activity and the impact of GLM retreatment after a disease flare, reinforces the currently labelled GLM dosing regimen (posology) for the nr-axSpA indication.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Wang and colleagues suggested that some AS patients' characteristics could vary the TNFi response; the probability of a major response increased with higher CRP levels and decreased with body mass index (60). A higher risk of disease flares in axSpA patients also seemed to be associated with a reduction in the dose of TNFi therapy, with no significant differences in infection rates or injection/infusion reactions (61). Some working-groups investigated the efficacy of TNFi throughout the application of imaging techniques.…”
Section: Tnf-alpha Inhibitorsmentioning
confidence: 99%